Feedback Menggunakan Telepon Genggam terhadap Latihan Mandiri Mahasiswa: Penelitian Kualitatif - Ide Pustaka Setiawan (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Feedback is usually delivered face to face, in appropriate manner and appropriate time (Dent & Harden, 2005), from instructor to the students during skills training session. But how the instructor gives feedback when the students conduct independent study? Could recording facility of students’ mobile phone (hand-phone) solve this problem? The aims of this study are to understand whether or not mobile phone could be used to provide feedback toward students’ independent study as well as to develop a process of giving feedback using mobile phone toward students’ independent study.Method: This was qualitative study. All first year students academic year 2010/2011 (n=400) were assigned to do independent study to practice communication skill, basic physical examination, vital sign examination toward 10 differently healthy person in community. During independent study, students asked to record their skill using video recording facility within their own mobile phone. The recording file from mobile phone was then burnt to the CD. Both peers and instructors asked to watch the students’ performance in VCD as well as to give written feedback which is equipped by structured questions. Survey as to feedback given to students toward both peers (n=49) and skills lab instructor (n=50) which are selected randomly was conducted. After receiving written feedback from both peers and instructors, students who perform in VCD were asked to make written reflection about feedback that is given to them.Results: All data obtained from survey were compiled. Three coders were assigned to analyze the data. They worked separately to look for the finding categories (open coding) assisted by atlas-ti 6.0 software. Coders meet frequently to discuss the finding and achieve agreement. The study yielded the following results: 1) feedback on skills feedback on quality of recording includes feedback on: video, recording tools, actor and setting, 3) Students’ reflection said that the feedback is useful; 4) There are suggestions to improve the recording result.Conclusion: 1) Mobile phone could be used to provide feedback toward students’ independent study, 2) Technical things should be noticed in order to get better quality of recording.